The Enhance Engagement Students Through Kahoot! In Online Lecture During Pandemi Covid-19 - Pipih Nurhayati (Jurnal Teknologi Pembelajaran, 2021)
Numerous schools worldwide have closed during Covid-19 pandemic but students has several distraction when they study from home. Schools and universities have to continue with preparing learning method in any occasion like online lecture. Some study results show an increase in linkages using digital applications, one of which is Kahoot. Therefore, this study aims to analyze the acceptance and relationship of students with lectures through Kahoot in online lecture. In this study, 67 students of pre-service Madrasah/ Primary teachers at a Siliwangi Islamic College were chosen as a participant. The age of the students ranged from 19 to 30 years and they were students who were taught by the researcher. The research conducted of two phases. In the first phases, consist of an introduction, lectures, and Kahoot! Quiz each chapter. In the second phase students answering the questionnaire-based online using google form. Question points in the questionnaire included usability, ease of use, attitude, engagement skills, and interaction. The findings show that a whole respondents agree that Kahoot can improve their learning performance. In spite of encourage in taking a good notes and listening carefully in classroom, Kahoot is contribute students to having fun in the online lecture.